Big Data in Homeland Security - Wang, Lidong; Alexander, Cheryl Ann (Journal of Information, 2015)
Big Data predicts outcomes and has great impacts on knowledge discovery and value creation. It can be used to fight against terrorism and enhance Homeland Security by providing accurate predictions and patterns of terrorist activities. This paper introduces some methods and technologies used in Homeland Security. They are: biometrics, radio frequency identification (RFID), data mining, cloud computing, and Big Data. Big Data applications in Homeland Security are presented. These applications include Big Data in general security and public safety, crime prediction and aviation security, disasters, and cybersecurity and cyber defense. Big Data challenges in security are also discussed.